Letter - Lodge, W.?
001-0127-001 Registered Office: 70 St. George's Square, London. S.W.1 CLERICAL & ADMINISTRATIVE WORKERS' UNION Incorporating the National Union of Clerks & Administrative Workers, and the Association of Women Clerks and Secretaries Head Office: 30 Clouston Street. Glasgow. N.W. Paisley Branch: 13 Porterfield Road, Renfrew 29 1 44 The Secretary, TUC Dear Sir, We have received an appeal from an organisation calling itself Hogar Espanol (Spanish Republican House) address 22 Inverness Terrace, London W.2. Could you let us know if this is a genuine Anti Fascist Organisation. Yours fraternally W. Lodge Secretary 292/946/1/127